Polyurethane/Silane-Functionalized ZrO2 Nanocomposite Powder Coatings: Thermal Degradation Kinetics - Farimah Tikhani (18768025) (2020)
A polyurethane (PU)-based powder coating reinforced with vinyltrimethoxysilane (VTMS)-functionalized ZrO2 nanoparticles (V-ZrO2) for thermal stability was developed. Chemical structure, microstructure and thermal degradation kinetics of the prepared coatings were investigated. The peak of aliphatic C–H vibrating bond in the Fourier transform infrared (FTIR) spectrum of V-ZrO2 was a signature of VTMS attachment. Scanning electron microscopy (SEM) images reveled that, by increase of V-ZrO2 content from 0.1 to 0.3 wt.% and then 0.5 wt.%, some agglomerations of nanoparticles are formed in the PU matrix. Thermogravimetric analysis (TGA) of the PU/V-ZrO2 powder coatings was performed at different heating rates nonisothermally to capture alteration of activation energy (Ea) of degradation of PU/V-ZrO2 powder coatings as a function of partial mass loss by using Friedman, Kissinger–Akahira-Sunose (KAS), Ozawa–Wall–Flynn (FWO) and modified Coats–Redfern isoconversional approaches. It was observed that by addition of 1 wt.% V-ZrO2 to PU resin the early state degradation temperature at 5% weight loss increased about 65 °C, suggesting a physical barrier effect limiting the volatility of free radicals and decomposition products. Incorporation of 5 wt.% ZrO2 led to about 16% and 10% increase in Ea and LnA of blank PU, respectively, which was indicative of higher thermal resistance of nanocomposite powder coatings against thermal degradation. There was also obvious agreement between model outputs and experimental data. The results reveal that nanocomposite coating shows superior thermal properties compared to neat PU powder coatings, and the presence of nano ZrO2 in sufficient amount causes retardation of the thermal decomposition process. Other Information Published in: Coatings License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/coatings10040413 Disclaimer: The University of Doha for Science and Technology replaced the now-former College of the North Atlantic-Qatar after an Amiri decision in 2022. UDST has become and first national applied University in Qatar; it is also second national University in the country.